2022
DOI: 10.3390/nu14204242
|View full text |Cite
|
Sign up to set email alerts
|

Association of Infant Feeding Indicators and Infant Feeding Practices with Coexisting Forms of Malnutrition in Children under Six Months of Age

Abstract: Breastmilk is the only recommended source of nutrition for infants below six months of age. However, a significant proportion of children are either on supplemental breastfeeding (SBF) or weaned due to the early introduction of solid/semi-solid/soft food and liquids (SSF) before six months of age. There is good evidence that exclusive breastfeeding (EBF) in infants below six months of age protects them from preventable illnesses, including malnutrition. The relationship between infant feeding practices and coe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Preceding studies evolved that a child of families with no education is more likely to have malnutrition (Ahmed et al, 2021; Babatunde & Qaim, 2010; Olwedo et al, 2008). A previous study exhibits a similar relationship between the coexistence of underweight with wasting and stunting and the education of mothers (Khaliq, Wraith, Miller, & Nambiar, 2022). This study has shown that the marital age of the mother is significantly associated with child malnutrition which is also corroborated by a survey conducted in rural areas of Nepal (Wells et al, 2022).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Preceding studies evolved that a child of families with no education is more likely to have malnutrition (Ahmed et al, 2021; Babatunde & Qaim, 2010; Olwedo et al, 2008). A previous study exhibits a similar relationship between the coexistence of underweight with wasting and stunting and the education of mothers (Khaliq, Wraith, Miller, & Nambiar, 2022). This study has shown that the marital age of the mother is significantly associated with child malnutrition which is also corroborated by a survey conducted in rural areas of Nepal (Wells et al, 2022).…”
Section: Discussionsupporting
confidence: 62%
“…Other remaining studies focused to identify factors linked to the double burden of malnutrition. Earlier research also explored the prevalence, patterns, and factors that cause the coexisting forms of malnutrition in neonates, infants, and children (Khaliq et al, 2021 ; Khaliq, Wraith, Miller, & Nambiar, 2022 ; Khaliq, Wraith, Nambiar, & Miller, 2022 ). In the context of Bangladesh, there is a lack of evidence focusing on the determinants of the presence of CFM considering the most recent countrywide survey BDHS‐2017/18 data.…”
Section: Introductionmentioning
confidence: 99%
“…We can postulate that exclusive breastfeeding (EBF) recommendation for children aged below six months can be one of the preponderant reasons for the low adherence among young children. During the EBF period, it is advisable to use ORS, medicine, multivitamins, and vaccines in conjunction with breast milk [ 32 , 33 ]. However, any solid, semi-solid, liquid, and soft food during the first six months of life reflect a deviation from the recommended feeding standards [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the EBF period, it is advisable to use ORS, medicine, multivitamins, and vaccines in conjunction with breast milk [ 32 , 33 ]. However, any solid, semi-solid, liquid, and soft food during the first six months of life reflect a deviation from the recommended feeding standards [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most reports suggest that a mother's education is recognized as a fixed parameter regardless of whether many mothers (who are economically and educationally limited) attend school after their children's births (De Silva & Sumarto 2018). For instance, in Indonesia, it was reported in some studies that higher levels of maternal education reduced malnutrition levels (maternal and child double burden) in rural areas (Khaliq et al 2022) and some cities in Indonesia (Mahmudiono et al 2016;Mitra et al 2020). Those studies highlight the importance of nutrition education among parents or caregivers to improve their awareness and knowledge, and in the long run, their attitudes and behaviours.…”
Section: Introductionmentioning
confidence: 99%